Exome sequencing discloses KALRN homozygous variant as likely cause of intellectual disability and short stature in a consanguineous pedigree. Issue 1 (December 2016) - Makrythanasis, Periklis; Guipponi, Michel; Santoni, Federico; Zaki, Maha; Issa, Mahmoud; Ansar, Muhammad; Hamamy, Hanan; Antonarakis, Stylianos
Abstract Background The recent availability of whole-exome sequencing has opened new possibilities for the evaluation of individuals with genetically undiagnosed intellectual disability. Results We report two affected siblings, offspring of first-cousin parents, with intellectual disability, hypotonia, short stature, growth hormone deficiency, and delayed bone age. All members of the nuclear family were genotyped, and exome sequencing was performed in one of the affected individuals. We used an in-house algorithm (CATCH v1.1) that combines homozygosity mapping with exome sequencing results and provides a list of candidate variants. One identified novel homozygous missense variant inKALRN (NM_003947.4:c.3644C>A: p.(Thr1215Lys)) was predicted to be pathogenic by all pathogenicity prediction software used (SIFT, PolyPhen, Mutation Taster).KALRN encodes the protein kalirin, which is a GTP-exchange factor protein with a reported role in cytoskeletal remodeling and dendritic spine formation in neurons. It is known that mice with ablation ofKalrn exhibit age-dependent functional deficits and behavioral phenotypes. Conclusion Exome sequencing provided initial evidence linkingKALRN to monogenic intellectual disability in man, and we propose thatKALRN is the causative gene for the autosomal recessive phenotype in this family.